Re-arranging formula rules

liz

New member
Joined
Mar 26, 2014
Messages
1
Hi,

I am just wondering why 9/5C - C = -32 becomes C(9/5-1) = -32 in the problem below? What is the rule that makes this so?

Screen Shot 2014-03-25 at 8.06.43 PM.jpg
 
Hi,

I am just wondering why 9/5C - C = -32 becomes C(9/5-1) = -32 in the problem below? What is the rule that makes this so?

View attachment 3964

Do you understand that:

a*(x + y) = a*x + a*y → this is called distributive property of multiplication.

The operation you refer to is in the "reverse direction" [ a*x + a*y = a * (x + y)].

It is also sometimes referred to as factorization (in your problem - recognizing common factor "c" and factoring it out).
 
Top